Consciousness in Jawless Fishes - Suzuki, Daichi G. (Frontiers in Systems Neuroscience, 2021)
Jawless fishes were the first vertebrates to evolve. It is thus important to investigate them to determine whether consciousness was acquired in the common ancestor of all vertebrates. Most jawless fish lineages are extinct, and cyclostomes (lampreys and hagfish) are the sole survivors. Here, I review the empirical knowledge on the neurobiology of cyclostomes with special reference to recently proposed “markers” of primary, minimal consciousness. The adult lamprey appears to meet the neuroanatomical criteria but there is a practical limitation to behavioral examination of its learning ability. In addition, the consciousness-related neuroarchitecture of larvae and its reconstruction during metamorphosis remain largely uninvestigated. Even less is known of hagfish neurobiology. The hagfish forebrain forms the central prosencephalic complex, and the homology of its components to the brain regions of other vertebrates needs to be confirmed using modern techniques. Nevertheless, as behavioral responses to olfactory stimuli in aquariums have been reported, it is easier to investigate the learning ability of the hagfish than that of the lamprey. Based on these facts, I finally discuss the potential future directions of empirical studies for examining the existence of consciousness in jawless fishes.